Spatial social value distributions for multiple user groups in a coastal national park. (1st May 2022) - Ancona, Zachary H.; Bagstad, Kenneth J.; Le, Lena; Semmens, Darius J.; Sherrouse, Ben C.; Murray, Grant; Cook, Philip S.; DiDonato, Eva
Abstract: Managing public lands to maximize societal benefits requires spatially explicit understanding of societal valuation, and public participation geographic information systems (PPGIS) are increasingly used in coastal settings to accomplish this task. Social Values for Ecosystem Services (SolVES), a PPGIS tool that systematizes the mapping and modeling of social values and cultural ecosystem services, is promising for use in coastal settings but has seen relatively limited applications relative to other PPGIS approaches; it has also, to our knowledge, not yet been applied in a barrier island setting. In this study, we surveyed two visitor groups and residents living near Cape Lookout National Seashore (North Carolina, USA) to understand their social values in the context of the park's management needs. We developed social-value models to evaluate differences between three user groups (fall visitors, summer visitors, and residents) and to evaluate how respondents' experiences, attitudes, and recreational activities influence the locations they value and their most strongly held value types, which included aesthetic, recreation, biodiversity, future, therapeutic, and historic values. We found that accessibility, user types and the seasonality of major recreational activities, and the linear configuration of the barrier island system at Cape Lookout are important influences on the social values held by visitors and residents. The modeling results provide information relevant to management at Cape Lookout and can inform the design of future PPGIS studies in coastal and marine settings. Highlights: Growing use of PPGIS to understand coastal ecosystem services. One-off studies predominate vs. use of tools like SolVES. We apply SolVES to a U.S. national seashore. Multiple analyses consider different user groups, activities, attitudes. Access, user types & seasonality, barrier island configuration influenced values.